Evaluation of the bacteriological quality of underground well water in Oyi local government area of Anambra State, Nigeria - Nvene, Victor Ositadinma; Ikevude, Chizaramoku Tochi; Okafor, Ugochukwu Chukwuma; Owhonda, Golden Chukwuemeka (International Journal Of Community Medicine And Public Health, 2023)
Background: Water is indispensable for man’s existence on earth. In urban and predominantly rural communities in Nigeria, with over 85% of the population living below an average income, traditional drinking water sources such as open reservoirs, springs and open wells are still being used. The study assessed the bacteriological qualities of underground well water in Oyi L.G.A of Anambra State. Methods: Water samples collected by random sampling from various wells in the selected thirteen (13) wards of the study area were subjected to bacteriological analysis using standard methods. The bacteriological analysis examined differential and presumptive coliform counts. Confirmatory coliform tests were carried out using a loopful of presumptive positive and negative tests already sub-cultured on MacConkey agar plate and incubated at 37 0c for 24 hours to obtain bacterial isolates. Results: Escherichia coli was the most frequently occurring isolate of all the bacteria identified. Other isolates include Streptococcus spp., Staphylococcus aureus, Shigella spp., Enterococcus spp., Salmonella spp., Pseudomonas spp., Proteus spp. and Bacillus spp. The majority of these organisms are Gram-negative microorganisms which are most times implicated in gastrointestinal abnormalities. Conclusions: There is a high incidence of contamination of well waters by pathogenic organisms in most well waters from the Study area. Underground well water sources to be utilized for domestic purposes such as cooking should be treated or disinfected before use, either by boiling and filtration or by chemical sterilization or a combination of both.